Words used by the breathless patient in COPD and enhancing therapeutic care. (2nd March 2021) - Harrison, Susan
Abstract : Shortness of breath, dyspnoea and breathlessness are collective terms to describe the awareness of inadequate gas exchange within the respiratory system. Varying mechanisms, behavioural and physiological changes are caused by this ventilation–perfusion mismatch. This complex sensation encompasses many diverse concepts. The spectrum of language and words used as a consequence of this sensation vary from quality and intensity to emotions and feelings. Matching the phrases to the cause supports understanding. Studies reviewed produced clusters of verbal descriptors which reflect the multidimensional input as a consequence of being out of breath. Using these clusters has produced a comprehensive list of twelve words known as 'The Dyspnoea 12' which, when used, quantifies the severity of this debilitating and extremely distressing symptom. Could these verbal descriptors be used to aid the assessment and treatment of their cause in service users and provide a more holistic view to a widespread problem?